Intersectionality in the Liminal Space: Researching Caribbean Women's Health in the UK Context - Andrews, Nicole; Greenfield, Sheila; Drever, William; Redwood, Sabi (Frontiers in Sociology, 2019)
African Caribbean women in the UK who are diagnosed with chronic illnesses that are related to overweight and obesity are more likely to experience poorer outcomes than their White British counterparts. It is then important to increase understandings of how women from this ethnic group perceive health with relation to body shape and size so that interventions can be developed to prevent the development of such conditions and to improve outcomes. As such, it is important to develop research methodology that encourages participation in health research from African Caribbean women and enables the capture of in-depth data that gives insight into the nuances of health understandings related to the body and the social realities in which they exist. This paper details the methodological framework of The Big Talk project, an investigation that sought to develop a novel approach to conducting health research with seldom heard communities. The concept of intersectionality, as used in Critical Race Theory, was applied as a theoretical tool for exploring the dynamics of societal power and where this power intersects across the lived realities of race, ethnicity, gender, sexuality, (dis)ability, and class. For this research, these intersections are explored for African Caribbean women and how they relate to concepts of health, body shape, and size. This research study was conducted in spaces identified as liminal spaces for African Caribbean women: talk radio programmes; hairdressing salons and; local community groups. A Black feminist epistemological approach was used to facilitate the collection of data. The data that emerged from these liminal spaces are not necessarily definitive answers on health for African Caribbean women, but rather illuminate alternative ways of understanding the social world from the perspective of those subject to power. This phenomenon makes liminal spaces intersectional in their construction and in taking such an approach to analysis could enable finely grained details of discourses regarding health, wellness and the body to be gathered. The importance of this understanding can help to improve preventive health interventions for African Caribbean women.